Reactive oxygen species (ROS) generation in sepsis - (:unkn) unknown (Society of Pharmaceutical Sciences of Ankara (FABAD), 2011)
Sepsis and septic shock remain as leading cause of death in adult intensive care units. It is widely accepted that sepsis and septic shock are caused predominantly by gram-negative bacteria and their endotoxins. Endotoxin or Lipopolysaccharide (LPS) have important roles as host responses and trigger the inflammatory processes, caused by gram-negative bacterial infection. Production of oxygen radicals by neutrophils and macrophages such as reactive oxygen species (ROS), NO (nitric oxide) and peroxynitrite promote gene expression of proinflammatory mediators. Enhanced generation of ROS well be responsible for tissue injury in septic shock and endotoxemia. Oxidative stress is defined as an unbalance between oxidants and antioxidants. Antioxidant capacity may be compromised in patients with severe infections and high levels of the metabolic products of free radical damage can be observed. The aim of this review is to inspect the play role of inflammatory mediators with oxidative stress is associated reactive oxygen species or reactive nitrogen species and the negative effects including DNA damage of sepsis pathogenesis.
Keywords: Oxidative stress; Sepsis